Compaction of highly porous granular matter by impacts on a hard wall - Ringl, Christian (2015)
Using a granular-mechanics code, we study the impact of a highly porous granular body on a hard wall. The projectile consists of monodisperse adhesive micrometer-sized silica grains. For the impact velocities studied, v<0.5m/s, the sample does not fragment, but is compacted. We find that the compaction is proportional to the impact speed. The proportionality constant increases with decreasing porosity. However, the compaction is inhomogeneous and decreases with distance from the target. A compaction wave runs through the aggregate; it slows down while the compaction becomes less efficient.